SOCIO-ECONOMIC ASPECTS OF NON CONVENTIONAL FEED UTILIZATION AMONG THE DAIRY FARMERS IN VELLORE DISTRICT OF TAMIL NADU - B. Rajesh Kumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study is planned to assess the socio-economic profile, cost economics in feeding and impact of brewery waste utilization among dairy farmers in Vellore district of Tamil Nadu. For this purpose, a survey was conducted in six blocks with one village per block and 15 farmers per village constituting a total of 90 respondents. Data was collected through personal interview method with the help of pretested interview schedule. The survey results indicated that majority of the farmers are in the age of 33 - 47 years and the family size of the respondents is less than 5. More than 50% of the farmers had experience of 10 years in dairy farming practices and the annual income from dairy farming was higher than agriculture sector. All farmers were providing their milch animals with green and dry fodder and the total cost incurred varied from Rs.38.97/- to Rs.29.53/day/animal during milch period and from Rs. 31.66/- to Rs.25.38/day/animal during the dry period. In concentrate mixture, the main ingredients reported were bran, husk, rice gruel and oil cakes and total cost incurred varied from Rs.112.74 to Rs.43.04/day/animal during milch period and from Rs.73.25 to Rs.24.95/day/ animal during the dry period. The mean milk production varied between 5.37 lts to 9.51 lts/day/animal and the cost/ltr of milk varied between Rs.13.50 to Rs.15.95/ltr. It is imperative to note that 38.89% of the farmers were utilizing unconventional feeds such as tapioca powder, tamarind seed, brewery waste and dried distillers’ grain soluble (DDGS) to feed their dairy cattle. Also, from the survey it is inferred that dairy farmers should be sensitised more on the scientific ways of feeding lactating dairy cattle to augment milk production and thereby to increase their livelihood security.